A tunable encoder with circular dichroism and polarization encoding function based on a layered metastructure in the GHz range - Chuan-Qi Wu; Jun-Yang Sui; Qi Chen; Xing-Zhou Tang; Hai-Feng Zhang (Materials & Design)
In this paper, based on a layered metastructure, a tunable encoder capable of circular dichroism (CD) and polarization conversion (PC) is researched, which contains one common medium, magnetized plasma, and yttrium iron garnet (YIG). The linear polarization waves (LPWs) are elected as incident waves. The incident angle and external magnetic field intensity are θ and HO. A modulable dielectric layer (MDL), composed of YIG, is optionally added to the preceding item of the given metastructure, which owns a certain thickness. By adjusting the proper θ, HO, and adding the MDL, the CD can be obtained at a certain frequency point, where the right-handed circular polarization waves (CPWs) and left-handed CPWs have different reflections. Meanwhile, the LPWs can be converted to CPWs or other polarization waves in a specific frequency band. Furthermore, the θ and addition of the MDL are considered as the first and second logic levels, respectively, to form four logic codes, which can realize the PC from LPWs to CPWs or LPWs within the same specific frequency band. Hence, the designed encoder has a promising potential in the precise control of PC in the special bandwidth, which can provide excellent support for the research of tunable and diverse polarization splitters and selectors.